The signaling role of fiscal austerity - Anna Gibert (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
I build a model where creditworthy countries may use fiscal austerity to communicate their ability to repay sovereign debt and show that the signaling channel is active only for high levels of asymmetric information. The model generates a negative association between the amount of public information, provided by the rating agencies, and fiscal tightness. Informed by the model predictions, I build a model where creditworthy countries may use fiscal austerity to communicate their ability to repay sovereign debt and show that the signaling channel is active only for high levels of asymmetric information. The model generates a negative association between the amount of public information, provided by the rating agencies, and fiscal tightness. Informed by the model predictions, I perform an empirical investigation based on a panel of 58 OECD and emerging market economies since 1980 and find evidence of this signaling channel.
Keywords: D82; E62; F34; G24; 330; signaling; fiscal austerity; sovereign debt; credit ratings